THE EFFECT OF LIQUIDITY, LEVERAGE, PROFITABILITY AND INSTITUTIONAL OWNERSHIP ON ENVIRONMENTAL COSTS IN GREEN INDUSTRY COMPANIES PERIOD 2019 – 2021 - Popon Rabia Adawia (Universitas Muhammadiyah Tangerang, 2023)
The aim of this research is to empirically test the influence of liquidity, leverage, profitability and institutional ownership on environmental costs in Green Industrial companies listed on the Indonesian Stock Exchange for the 2019-2021 period. The research method is quantitative associative causal. The population is 23 companies that have won awards as green industry (PROPER Green and Gold categories) and the sample is 18 companies for the 2019-2021 period. Samples were taken based on purposive sampling. The dependent variable is environmental costs and the independent variables are liquidity, leverage, profitability and institutional ownership. The method used in testing this hypothesis is panel data regression analysis processed using eviews 10 software with t-test then f-test with a significance level of five percent and the coefficient of determination test. The research results show that environmental costs are positively and significantly influenced by liquidity and profitability. Leverage has a negative and insignificant effect on environmental costs. Meanwhile, institutional ownership does not influence and is not significant to environmental costs. The variables liquidity, leverage, profitability and institutional ownership simultaneously have a positive & significant effect on environmental costs in green industry companies listed on the Indonesia Stock Exchange for the 2019-2021 period.